Ovarian Juvenile Granulosa Cell Tumor in A 2.5 Years-Old Girl: The Importance of Early Diagnosis - Boughdir, Malak; daib, Aida; Ben abdallah, Rabiaa; Chebab, Fatma; Tlili, Sameh; hellel, Youssef; kaabar, nejib (Iranian Journal of Pediatric Surgery, 2023)
Juvenile granulosa tumor is a rare tumor in infant. The diagnosis should be discussed in any ovarian tumor of children, especially in front of the early signs of puberty. The prognosis of granulosa cell tumors remains good. The main prognostic factor is the stage of local extension. Early diagnosis at early signs of puberty is an important prognostic factor. We describe the case of a girl aged 2 years and 5 months who presented signs of early puberty. The diagnosis was a secreting ovarian tumor but was very large at that time. We focus by this observation on the value of early diagnosis of this tumor type which remains a key prognostic factor.